Readiness to change among involuntarily and voluntarily admitted patients with substance use disorders - Anne Opsal; Øistein Kristensen; Thomas Clausen (BMC, 2019)
Abstract Background Health care workers in the addiction field have long emphasised the importance of a patient's motivation on the outcome of treatments for substance use disorders (SUDs). Many patients entering treatment are not yet ready to make the changes required for recovery and are often unprepared or sometimes unwilling to modify their behaviour. The present study compared stages of readiness to change and readiness to seek help among patients with SUDs involuntarily and voluntarily admitted to treatment to investigate whether changes in the stages of readiness at admission predict drug control outcomes at follow-up. Methods This prospective study included 65 involuntarily and 137 voluntarily admitted patients treated in three addiction centres in Southern Norway. Patients were evaluated using the Europ-ASI, Readiness to Change Questionnaire (RTCQ), and Treatment Readiness Tool (TReaT). Results The involuntarily admitted patients had significantly lower levels of motivation to change than the voluntarily admitted patients at the time of admission (39% vs. 59%). The majority of both involuntarily and voluntarily admitted patients were in the highest stage (preparation) for readiness to seek help at admission and continued to be in this stage at discharge. The stage of readiness to change at admission did not predict abstinence at follow-up. The only significant predictor of ongoing drug use at 6 months was SUD severity at baseline. Conclusions The majority of involuntarily admitted patients scored high on motivation to seek help. Their motivation was stable at a fairly high level during their stay, and even improved in some patients. Thus, they were approaching the motivation stage similar to the voluntarily admitted patients at the end of hospitalization. Therapists should focus on both motivating patients in treatment and adapting the treatment according to SUD severity. Trial registration ClinicalTrials.gov, NCT00970372. Registered 1 September 2008, https://clinicaltrials.gov/ct2/show/NCT00970372. The trial was registered before the first participant was enrolled. The fist participant was enrolled September 02, 2009.